FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PENYIDIK DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI - Yuliani Yuliani; Liswandi Liswandi (JURNAL LENTERA BISNIS, 2022)
This research was conducted at the Special Crime Directorate of the National Police Criminal Investigation Unit. As for the formulation of the problem, namely: (1) how is the effect of work-family conflict and work stress on the Investigator's Motivation; (2) how the effect of work-family conflict and work stress on the performance of investigators; (3) how does work motivation affect the performance of investigators; and (4) how the effect of work-family conflict and work stress on the performance of investigators through work motivation. This research was conducted in a cross-sectional manner using a causal relationship to test the hypothesis. Using primary data obtained directly by distributing questionnaires to 139 investigators. Data analysis used Structural Equation Mode (SEM) which was processed with PLS version 3. The results of the analysis were used to determine the extent to which independent variables, namely work-family conflict and work stress, affected the dependent variables, namely investigator performance and work motivation: (1) Work-family conflict and stress that negatively and significantly affect work motivation; (2) work-family conflict and work stress negatively and significantly affect investigators; (3) work motivation affects the investigation positively and significantly; and (4) work-family conflict and work stress affect investigators negatively and significantly affect work motivation.Keywords: Work-FamiIy ConfIict, Job Stress, Motivation, Investigator Performance.